Content and Form of Pledge Contract in the Civil Law of the Russian Federation - NETISHINSKAYA, SorinLyubov F.; GUSHCHINA, Lyudmila I.; SHEKHOVTSOVA, Anna S.; KOLESNIKOVA, Viktoria A. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).33, 2018)
The article presents new provisions of the Civil Code of the Russian Federation on pledge, in particular, on conditions, forms of a pledge agreement, as well as on state registration and registration of pledge. We analyzed the provisions concerning the form of the pledge agreement, the state registration and registration of the pledge. The analysis revealed cases of establishing legal requirements in accordance with the notarial form of the pledge agreement. It is concluded that the agreement on real estate pledge is no longer subject to state registration, and therefore the provisions of the Civil Code of the Russian Federation on state registration and registration of collateral are particularly urgent and require further study, as well as other legislative acts of the Russian Federation. Based on these studies, cases are indicated where the pledge is subject to state registration. The procedure and conditions for state registration of the pledge of exclusive rights are also indicated for the results of intellectual activity and means of individualization. We have now announced the possibility of registering a pledge of other non-residential assets through registration in order to notify the pledge in the register of pledge notices of movable property and at the same time pay attention to the fact that the mortgagee with respect to a third party can refer to the right of pledge belonging to He only from the date of entry of a record of registered pledge.